Parental Age and the Risk of Cleft Lip and Palate in a Nigerian Population - A Case–Control Study - James, Olutayo (Ann Maxillofac Surg, 2020)
INTRODUCTION: Orofacial clefts are one of the most common congenital malformations in the facial region. Older maternal or paternal age presents higher odds of a child with an orofacial cleft. The objective of the study was to assess the association between parental age and risk of orofacial cleft. MATERIALS AND METHODS: This was a case–control study among 110 parents of children with orofacial cleft (case group) and 110 parents of children without orofacial cleft (control group). Information on maternal age, paternal age, and type of orofacial cleft in the children were obtained. The results were analyzed using descriptive statistics, Chi-square analysis, and bivariate logistic regressions to measure the association between parental age and orofacial cleft. The value of P was <0.05, with a 95% confidence interval (CI). RESULTS: Information on 219 children (109 cases and 110 controls) was analyzed, of which 52% were females. One respondent from the case group withdrew from the study. The odds of a child with orofacial cleft was statistically significantly lower in mothers aged 26–35 years compared to mothers aged 25 years and less (odds ratio [OR]: 0.32; 95% CI: 0.16, 0.79). Similarly, fathers aged above 35 years had statistically significantly lower odds of children with orofacial cleft than those 25 years and less (OR: 0.18; 95% CI: 0.02, 0.99). DISCUSSION: Our findings suggest that mothers aged 26-35 years may have lower odds of giving birth to babies with orofacial clefts, compared to younger mothers. Similarly, fathers aged above 35 years may have lower odds of giving birth to a child with orofacial cleft compared to fathers aged 25 years and less.